EXPERIENCE REPORT: PHYSICAL ACTIVITY AND HEALTHY EATING (Fiep Bulletin - online, 2013)
This work results from lived experience during the stage of physical education course in the second cycle of basic education, to experience this basement was used pedagogy projects, where instead of developing lesson plans, we will advise and collaborate so that students a certain class of the second cycle of basic education at a particular school in the municipality of Santana do Ipanema, Alagoas.With the completion of classes and dance practice futsal could enter more than 60 students of both sexes, students who were excluded from physical education classes for the school is preparing for a state competition.Performing the futsal tournament the many students had the opportunity to experience a competition, with the health fair, not only students, school staff, but also how the community had the opportunity to acquire new knowledge.It is a suggestion that the school develop more jobs where students can truly collaborate in the construction, the school increasingly bring the community into the school, students are motivated to be critical agents that school management, teachers use problems social relevance to guide students.
Keywords: pedagogy projects; physical activity and healthy eating.